Mapeamento do fluxo de valor para redução de lead time em uma indústria farmacêutica no norte do Paraná - Andrade, Gustavo Henrique de (2019)
The pharmaceutical industry has seen a significant evolution in recent years, as the expansion of health spending is growing. The purpose of the work is to make the search options improve the productive process of the company located in northern Paraná, so that it is aware of the removal of waste and a continuous process. This brings increased execution, reduced costs and fast delivery, so your recovery in the market is quick. To this end, using the lean mindset tool that is Value Stream Mapping, no understanding of the process as a whole is essential for improvement actions packed together with the goal. Reducing intermediate stocks, balancing what is produced and what is required, and the scope for zero waste processes is the way to decrease lead time. Having a satisfactory result for the product in question, it can be expanded to other product families used by the company.